Review of Heather Wiebe. 2012. Britten’s Unquiet Pasts: Sound and Memory in Postwar Reconstruction. New York: Cambridge University Press - Penner, Nina (Current Musicology, 2013)
Britten as a public figure. Britten as a composer of music for children, amateurs, and the church. These are sides of Britten’s legacy that have attracted little scholarly attention prior to Heather Wiebe’s recent monograph Britten’s Unquiet Pasts: Sound and Memory in Postwar Reconstruction. More familiar is Britten as a composer of opera and art song, and as a man “at odds with . . . society” (Pears 1983: 152).1 Although anticipating the Britten centenary by one year, Britten’s Unquiet Pasts is much in keeping with the spirit of other Britten publications to be released this year, not least Paul Kildea’s (2013) biography. What emerges from these new perspectives is a more complex view of Britten, both as an artist whose breadth of work defies easy classification, and as a man with changing and often conflicting impulses towards his envisaged role in society.